Early laser surgery is not associated with very preterm delivery or reduced neonatal survival in TTTS. (3rd August 2021) - Espinoza, J.; Belfort, M. A.; Shamshirsaz, A. A.; Nassr, A. A.; Sanz Cortes, M.; Donepudi, R.; Espinoza, A. F.; Ostovar‐Kermani, T. G.; Johnson, R.; Harman, C.; Turan, O.
ABSTRACT: Objective: To evaluate the association of laser photocoagulation of placental anastomoses (LPA) prior to 18 weeks' gestation (early LPA) with very preterm delivery and neonatal survival in pregnancies with twin–twin transfusion syndrome (TTTS). Methods: This was a retrospective cohort study of monochorionic diamniotic twin pregnancies with TTTS undergoing LPA between 2002 and 2018 at two institutions. The rates of delivery < 28, < 30 and < 32 weeks' gestation, preterm prelabor rupture of membranes (PPROM) and 30‐day survival of one or both infants were compared between pregnancies undergoing early LPA and those undergoing LPA ≥ 18 weeks' gestation. Regression analysis was performed to determine the association of early LPA with very preterm delivery and 30‐day survival, adjusted for Quintero stage, study phase, selective fetal growth restriction, gestational age at delivery, maternal age ≥ 35 years, body mass index > 35 kg/m 2, placental location, use of Seldinger method to place the operative trocar, size of the trocar, participating center, use of Solomon technique, cerclage and PPROM. Survival analysis using the Cox proportional hazard model was applied to examine the LPA‐to‐delivery interval according to the timing of surgery, adjusted for confounding variables. Results: A total of 414 TTTS pregnancies were included in the study, of which 68 (16.4%) underwent early LPA. In the total cohort, the incidence of delivery at < 28, < 30 and < 32 weeks' gestation was 22.7%, 39.6% and 53.4%, respectively. Survival of both twins and survival of at least one twin at 30 days were 67.5% and 90.8%, respectively. No significant difference was noted between pregnancies that underwent early LPA and those that had LPA ≥ 18 weeks in the rate of delivery < 28 weeks (19.1% vs 23.4%; P = 0.4), < 30 weeks (38.2% vs 39.9%; P = 0.8) and < 32 weeks (44.1% vs 55.2%; P = 0.1) and PPROM (29.0% vs 24.1%; P = 0.4), or in the incidence of double‐twin survival (63.9% vs 68.1%; P = 0.5) and survival of at least one infant (91.8% vs 90.6%; P = 0.7) at 30 days. Early LPA was not associated with very preterm delivery or neonatal survival in the regression analyses. Early LPA was associated with a longer LPA‐to‐delivery interval compared with LPA performed ≥ 18 weeks (median, 106.9 days (range, 2–164 days) vs median, 69.3 days (range, 0–146 days); P < 0.001) when adjusted for confounding variables (hazard ratio, 2.56 (95% CI, 1.76–3.73); P < 0.001). Conclusion: Laser surgery before 18 weeks is not associated with an increased rate of very preterm delivery and PPROM or with reduced neonatal survival when compared with LPA after 18 weeks. © 2020 International Society of Ultrasound in Obstetrics and Gynecology